Observation of an action with a congruent contextual background facilitates corticospinal excitability: A combined TMS and eye-tracking experiment. (October 2018) - Riach, Martin; Holmes, Paul S.; Franklin, Zoë C.; Wright, David J.
Abstract: Action observation produces activity in similar regions of the brain to those involved in action execution and can offer an effective intervention for motor (re)learning, although optimal viewing conditions for such interventions remain to be established. In this experiment, single-pulse transcranial magnetic stimulation (TMS) and eye-tracking were used simultaneously to investigate the effect of manipulating background context on both corticospinal excitability and visual attention during action observation. Twenty-four participants observed four different videos: (i) a static hand holding a sponge (control condition); and an index finger-thumb pinch of a sponge against (ii) a plain black background; (iii) a background containing objects that were incongruent with the observed action; and (iv) a background containing objects that were congruent with the observed action. TMS was delivered to the hand representation of the left primary motor cortex, and motor evoked potentials were recorded from the first dorsal interosseous and abductor digiti minimi muscles of the right hand. Eye movements were recorded throughout the experiment. Results indicated that corticospinal excitability was facilitated during the congruent context condition compared to both the static hand and plain black background conditions. In addition, the number of fixations and percentage of time participants spent fixating on the background scene were significantly greater during the incongruent and congruent conditions compared to the static hand and plain black background conditions. These results indicate that the provision of additional visual information that is congruent with the observed movement contributes to a facilitation of corticospinal excitability by providing the observer with information regarding the goal and intention of the observed action. Providing congruent contextual information may enhance the efficacy of action observation interventions for motor (re)learning. Highlights: Action observation with a congruent context facilitated corticospinal excitability. Observation with incongruent or plain backgrounds did not facilitate MEP amplitude. Providing contextual information modulated visual attention during observation. Observation interventions should be presented with congruent contextual backgrounds.